Meaning-based coping, chronic conditions and quality of life in advanced cancer & caregiving. - Ellis, Katrina R; Janevic, Mary R; Kershaw, Trace; Caldwell, Cleopatra H; Janz, Nancy K; Northouse, Laurel (Psycho-oncology, 2016)
This study examined the relationship between the number of co-existing health problems (patient comorbidities and caregiver chronic conditions) and quality of life (QOL) among patients with advanced cancer and their caregivers and assessed the mediating and moderating role of meaning-based coping on that relationship.